The effect of flexible working arrangements and digital workplace on employee loyalty with employee satisfaction as mediation - Miqdarsah, Malikulqadr; Indradewa, Rhian (Jurnal Ekonomi dan Bisnis, 2024)
At this time, many companies are starting to carry out their business activities after going through the pandemic. All of these activities aim to achieve the company's main goal in the field of HRM, which is to increase employee satisfaction and loyalty. This study analyzes the relationship between the influence of flexible and digital work environments on employee satisfaction and employee loyalty in IT companies in Jakarta, Indonesia. The respondents of this study were 165 IT employees in Jakarta. This research was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). This research found that flexible working arrangements and digital workplaces positively affect employee satisfaction and loyalty. Employee satisfaction has a positive effect on employee loyalty. Employee satisfaction can mediate the relationship between flexible working arrangements, digital workplaces, and employee loyalty. Researchers can then consider research in other industries or sectors.